Opportunities Of Artificial Intelligence In Education - Abdullayeva Iroda Makhmudjanovna (Genius Journals, 2024)
This article examines AI's potential programs in education, clarifying its current state and future prospects. Through a comprehensive analysis of the literature, we study the various methods and technologies that artificial intelligence brings to the field of Education, discuss the results achieved so far and give insight into the impact of artificial intelligence for the future of Education. The article concludes with proposals to integrate artificial intelligence into education to improve educational outcomes.
Keywords: artificial intelligence; education; machine learning